Community-based breeding programs upscaled in Ethiopia and other African countries through partners - CGIAR Research Program on Livestock (2019)
The International Center for Agricultural Research in the Dry Areas (ICARDA)-led community-based breeding program (CBBP) has become the Ethiopia government’s strategy of choice for small ruminant genetic improvement. The program was incorporated in the country’s livestock master plan, receiving a USD 560,000 investment to upscale across the country. The genetic gains and socio-economic successes of the programs have led to their adoption and implementation by various partners in Uganda, Malawi, Liberia, South Africa and Burkina Faso